Perspective on rural health care - Sharma, Bharati (2005)
Health is a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity. The enjoyment of the highest attainable standard of health is one of fundamental right of every human being without distinction of race, religion, political belief, economic or social condition. -Reproduced.
Keywords: Health services